1993
DOI: 10.1093/cvr/27.7.1380
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adhesion to human vascular endothelium is modulated by constitutive and cytokine induced nitric oxide

Abstract: Inhibition of NO synthesis by L-NMMA potentiates platelet adhesion to unstimulated SGHEC-7 cells, showing that basally released NO regulates platelet adhesion. Stimulation of SGHEC-7 cells by cytokines increases their adhesive properties but at the same time causes them to express the inducible NO synthase. Nitric oxide generated by this enzyme contributes to the modulation of the adhesive properties of the endothelial cells. Thus both constitutive and inducible NO synthases modulate endothelial cell thromboge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(99 citation statements)
references
References 0 publications
4
92
0
2
Order By: Relevance
“…NADH and NADPH oxidase activity was measured according to the method described by Rajagopalan et al, 25 who demonstrated that this assay specifically measures NAD(P)H oxidase-generated superoxide. Briefly, platelets were homogenized by freeze and thawing, as described above.…”
Section: Nadh/nadph Oxidase Activitymentioning
confidence: 99%
“…NADH and NADPH oxidase activity was measured according to the method described by Rajagopalan et al, 25 who demonstrated that this assay specifically measures NAD(P)H oxidase-generated superoxide. Briefly, platelets were homogenized by freeze and thawing, as described above.…”
Section: Nadh/nadph Oxidase Activitymentioning
confidence: 99%
“…Human tumour cell lines SW480, SW620, DLD-l AssaYs of NOS activit} NOS activity was determined by measuring the rate of conversion of L-[U-'4C]arginine to [U-14Clcitrulline by soluble cytosolic extracts of the cells (Radomski et al. 1993).…”
Section: Cell Linesmentioning
confidence: 99%
“…NO is synthesized from conversion of L-arginine to L-citrulline by a family of NO synthases (NOS), which include constitutive and inducible isoforms (Moncada et al, 1991). Basal release of NO by endothelial cells contributes to the maintenance of normal vasodilatory tone and thromboresistance (Radomski et al, 1987(Radomski et al, , 1993. Previously, Shultz and Raij (1992) demonstrated that rats given a low dose of endotoxin exhibit a marked increase in the urinary excretion of NO metabolites and no evidence of glomerular thrombosis.…”
mentioning
confidence: 99%